Delivery of Pharmacogenetic Testing with or without Medication Therapy Management in a Community Pharmacy Setting - Haga SB; Mills R; Moaddeb J; Liu Y; Voora D (Dove Medical Press, 2021)
Susanne B Haga, Rachel Mills, Jivan Moaddeb, Yiling Liu, Deepak Voora Center for Applied Genomics & Precision Medicine, Duke University School of Medicine, Durham, NC, 27708, USACorrespondence: Susanne B Haga Email Susanne.haga@duke.eduObjective: The delivery of pharmacogenetic (PGx) testing has primarily been through clinical and hospital settings. We conducted a study to explore the feasibility of delivering PGx testing through community pharmacies, a less-studied setting.Methods: We conducted a cluster randomized trial of community pharmacies in North Carolina through two approaches: the provision of PGx testing alone or PGx testing with medication therapy management (MTM).Results: A total of 150 patient participants were enrolled at 17 pharmacies and reported high satisfaction with their testing experience. Participants in the PGx plus MTM arm were more likely to recall a higher number of results (p=0.04) and more likely to clearly understand their choices for prevention or early detection of side effects (p=0.01). A medication or dose change based on the PGx results was made for 8.7% of participants.Conclusion: Limited differences were observed in the provision of PGx testing as a standalone test or combined with MTM. A limited number of treatment changes were made based on PGx test results. Patient acceptance of PGx testing offered through the community pharmacy was very high, but the addition of MTM did not impact patient-reported perceptions about PGx testing or medication adherence.Keywords: pharmacy, pharmacogenetic testing, feasibility, patient experience